Compression and focussing a laser produced plasma using a plasma optical system - LUNNEY, JAMES (My University, 2012)
Axi-symmetric compression and focusing of a low temperature laser produced copper plasma with an electrostatic plasma optical system was investigated for the first time. The degree of plasma concentration was quantified using Langmuir ion measurements of the ion flow and optical measurements of the thickness distributions of copper depositions on glass substrates. Both the ion flow and the deposition measurements showed strong concentration of the ion-plasma flow towards the axis. The ion current density at the focus was compressed by a factor up to 9.The on-axis deposition rate was increased by about the same factor.
PUBLISHED
Keywords: electrostatic plasma optical system; electrostatic plasma optical system